The use of accelerometers to quantify collisions and running demands of Rugby Union match-play - Roe, G.; Halkier, M.; Beggs, C.; Till, K.; Jones, B. (International Journal of Performance Analysis in Sport, 2016)
This study examined the relationship between accelerometer metrics and both collisions and running demands during rugby union match-play. Twelve under-18 forwards and 14 under-18 backs were recruited from a professional rugby union club. Six competitive matches were filmed during which players wore micro-technological units (Optimeye S5, Catapult Innovations, Melbourne, Australia). Video footage was analysed for total collisions, while GPS data was analysed for total distance. Accelerometer metrics analysed were Player load™ (PL), Player Load™ 2D (PL2D), and Player Load™ slow (PLslow). A total of 81 player observations were included in the final analysis. Data were analysed using ordinary least squares regression. A 10-fold cross validation analysis was used to validate the findings. All PL variables demonstrated very large relationships with collisions in the forwards, while PLslow demonstrated the largest relationship (large) with collisions in the backs. Therefore, based on the strong relationship in both forwards and backs, PLslow may provide the most useful metric for measuring collision-based activity in both positional groups during match-play. Additionally, nearly perfect and very large relationships were observed between PL and total distance for forwards and backs respectively, suggesting that PL can be successfully used to quantify running demands when other methods are unavailable, for example during indoor training.